6ER-029 Eye drops of interferon alpha-2b to treat ocular pathologies. Issue 1 (23rd March 2023) - Serrano, M; López-Aspiroz, E; García-Martín, E; Barro-Ordovas, JP; Martínez-Hernández, A
Abstract : Background and Importance: Interferon alpha-2b is an option of treatment in malignant ocular pathologies such as ocular squamous surface neoplasia (OSSN) but its use is less extended to benign diseases like pterygium. In our country we had available Introna ® to made eye drops until 2021 June, but its production was discontinued and another drug (Bioferon ® ) with few data of safety in ocular administration was imported. Aim and Objectives: To evaluate the efficacy and safety of two different drugs (Introna ® and Bioferon ® ) in the treatment of ophthalmic pathologies. Material and Methods: All patients who underwent treatment with eye drops of interferon alpha-2b in our hospital from April of 2009 until August of 2022 were selected. We registered age, type of pathology, time of treatment, adverse events, recurrences and response (partial, complete or surgery immediately after or before treatment). A literature search was done to make the eye drops from Bioferon ® and finally we used water for injection to reconstitute the vial and balanced saline solution to complete 10 mL of volume (concentration of 10 mg/mL). Results: Thirty-six patients received 38 treatments (two patients had both eyes affected). By type of pathology, 24 were pterygium, 8 OSSN, 2 papilloma, 1 epidermoid carcinoma and 1 clear cell carcinoma. From the total of patients with pterygium, 54% received surgery, 21% had partial response and 25% had no response; four patients with malignant pathology (OSSN and carcinomas) had complete response, 2 had partial responses and 4 were operated. All patients with papilloma underwent surgery. On groups of malignant pathology and papilloma 1 patient had recurrence at each one. Evaluation of recurrences in pterygium group was hard due to lack of follow up after surgery, but with the data available 70% of them had no recurrences. Only one of all patients had an adverse event (ocular irritation). Two patients received Bioferon ®, both with OSSN. One had complete response and the other partial response with no adverse effects. Conclusion and Relevance: We can conclude that eye drops of interferón alfa-2b are safe and effective to treat malignant pathologies and the formulation with the new drug Bioferon seems to maintain safety and efficacy, but we need more patients to confirm it. References and/or Acknowledgements: Conflict of Interest: No conflict of interest.